Four mice deep in the jungle - Stilton, Geronimo (New Delhi Scholastic, 2004)
I have never been a brave mouse but lately my fears were talking over my life! So Thea and Trap decided to cure me. They dragged me away on an airplane all the way to the jungle. There I was forced to eat bug soup climb trees as tall as skyscrapers swim in raging rivers and even wrangle snakes. How would a fraidy mouse like me ever survive?
Keywords: Children Fiction